Pendidikan Moderasi dalam Haji (Studi Fenomenologi Kasus Haji) - Zakiyyah, Intan (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2023)
This article describes instances of violence in the holy land, which occur due to an understanding of fiqh studies rooted in a single normative approach. If fiqh studies are understood solely from a normative perspective, they result in a religious comprehension devoid of spiritual depth, emphasizing individual piety that is disconnected from social piety and a lack of moderate viewpoints. In contrast, Islam demands harmonious relationships with both Allah and fellow human beings. Therefore, fiqh studies require diverse approaches, such as phenomenological, philosophical, psychological, sociological, and others. This research specifically examines the phenomenon of violence in the holy land through a phenomenological approach, as there are no conclusive findings regarding cases of violence in the holy land. Such cases necessitate more complex studies. Based on the phenomena presented in this paper, violence in the holy land stems from a narrow and less moderate understanding of fiqh. The aim of this study includes urging scholars to provide guidance and solutions through the lens of sharia, a moderate perspective on pilgrimage, and considerations for collective well-being. The ultimate goal is to reduce violence in the holy land each year, ensuring that pilgrims feel safe and peaceful while performing the hajj.